Tribocorrosão da liga TI6AL4V em solução salina tamponada com fosfato Tribocorrosion of TI6AL4V alloy in phosphate buffered saline solution - Taíse M. Manhabosco; Iduvirges L. Muller; Claudia B. dos Santos (Química Nova, 2009)
The tribocorrosion behavior of Ti6Al4V alloy was investigated in a Phosphate Buffered Saline (PBS) solution by a reciprocating wear, using alumina ball as the counterface material, at different normal forces and sliding velocities. Dry wear experiments were performed in order to compare with the tribocorrosion experiments at open circuit potential and under anodic polarization. Dry wear induced a superior damage on the counterface, forming larger and shallower wear tracks compared with those experiments performed in PBS solution. The anodic current was increased by wear; however the volume of oxidized metal in tribocorrosion experiments correspond to a relative low percentage of the wear track volume.